Immobilization of UDP‐Galactose on an Amphiphilic Resin - Bevan, Jessica G. M.; Lourenço, Eva C.; Chaves‐Ferreira, Miguel; Rodrigues, João A.; Rita Ventura, M. (European journal of organic chemistry, 2018)
Nucleotide sugars are activated sugar precursors used by glycosyltransferases to form glycans. Here we report the first examples of resin‐bound nucleotide sugars: fluorinated UDP‐galactose and UDP‐galactose. They were conjugated to a polyethylene glycol resin through the C6 position with an SMCC linker in good to excellent yields. This synthesis represents an efficient method to access resin‐bound nucleotide sugars in a modular approach that enables modifications of the sugar or nucleotide before conjugation. The system has been conceived as a new chemistry‐based screening system for enzymes that use UDP‐galactose. Here we report the first example of resin‐bound nucleotide sugars: fluorinated UDP‐Galactose and UDP‐Galactose. This synthesis represents an efficient method to access resin‐bound nucleotide sugars in a modular approach that enables modifications of the sugar or nucleotide before conjugation.